2.7k views
3 votes
Question 1 options:
f(x) = -2x-1

f(-2) =

Question 1 options: f(x) = -2x-1 f(-2) =-example-1
User AziMez
by
4.7k points

2 Answers

4 votes

Answer:

-5

Explanation:

f(×)=2x-1

f(-2)=2×(-2)-1 (here,x= -2)

=-4-1

= -5

User Vaughn Cato
by
5.2k points
4 votes

Answer:

f(-2) = 3

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Function Notation

Explanation:

Step 1: Define

f(x) = -2x - 1

f(-2) is x = -2

Step 2: Evaluate

  1. Substitute: f(-2) = -2(-2) - 1
  2. Multiply: f(-2) = 4 - 1
  3. Subtract: f(-2) = 3
User Kronus
by
5.6k points